2015
DOI: 10.5204/ijcjsd.v4i2.211
|View full text |Cite
|
Sign up to set email alerts
|

Cultures of Abuse: ‘Sex Grooming’, Organised Abuse and Race in Rochdale, UK

Abstract: Revelations of organised abuse by men of Asian heritage in the United Kingdom have become a recurrent feature of international media coverage of sexual abuse in recent years. This paper reflects on the similarities between the highly publicised 'sex grooming' prosecutions in Rochdale in 2012 and the allegations of organised abuse in Rochdale that emerged in 1990, when twenty children were taken into care after describing sadistic abuse by their parents and others. While these two cases differ in important aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Online grooming is also referred to as 'cybersexploitation', and the case studies fit the patterns reported in this research: the groomer was first focused on building relationships but then progressed to conversations of a sexual nature that included behaviours that were controlling, aggressive and/or coercive. 27 The current literature is overrepresented by cases in which the groomer is part of a larger organized group, 28 whilst this paper looks at the under-represented cases where young women were groomed by one man who was not part of an organized group (as far as the researchers were aware).…”
Section: Conceptualizing Online Grooming Behavioursmentioning
confidence: 99%
“…Online grooming is also referred to as 'cybersexploitation', and the case studies fit the patterns reported in this research: the groomer was first focused on building relationships but then progressed to conversations of a sexual nature that included behaviours that were controlling, aggressive and/or coercive. 27 The current literature is overrepresented by cases in which the groomer is part of a larger organized group, 28 whilst this paper looks at the under-represented cases where young women were groomed by one man who was not part of an organized group (as far as the researchers were aware).…”
Section: Conceptualizing Online Grooming Behavioursmentioning
confidence: 99%
“…Minority men are frequently presented as representatives of their communities; white men are more likely to be seen as individual aberrations (Salter & Dagistanli, 2015;Shier & Shor, 2016). In the former case, it is the group who are deemed monstrous; in the latter, it is the individual.…”
Section: Read All About It?mentioning
confidence: 99%
“…There is not room here to discuss these UK cases; suffice to note, there is ample evidence that such egregious crimes are not unique to Muslim communities in Britain, and that there is nothing inherently 'Muslim' about them. The Islamophobia of the public discussion of these cases has been well analysed by Tufail (2015Tufail ( , 2018, Salter and Dagistanli (2015) and Patel (2018). It is demonstrable that the racialised reporting of both the Australian and the British cases motivated repeated instances of Islamophobic hate crime, including murder, in both IJCJ&SD 83 www.crimejusticejournal.com 2020 9(2)…”
Section: A New Definition and Analysismentioning
confidence: 99%